2015
DOI: 10.1128/jvi.02980-14
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome-Associated Coronavirus Vaccines Formulated with Delta Inulin Adjuvants Provide Enhanced Protection while Ameliorating Lung Eosinophilic Immunopathology

Abstract: Although the severe acute respiratory syndrome-associated coronavirus (SARS-CoV) epidemic was controlled by nonvaccine measures, coronaviruses remain a major threat to human health. The design of optimal coronavirus vaccines therefore remains a priority. Such vaccines present major challenges: coronavirus immunity often wanes rapidly, individuals needing to be protected include the elderly, and vaccines may exacerbate rather than prevent coronavirus lung immunopathology. To address these issues, we compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
231
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(244 citation statements)
references
References 53 publications
(68 reference statements)
4
231
3
2
Order By: Relevance
“…Intranasal vaccination with the RBD domain of the MERS-CoV S protein induced much stronger local mucosal immune responses in the lung than subcutaneous immunization (Ma et al, 2014a). Other studies showed that full-length monomeric or trimeric recombinant SARS-CoV and MERS-CoV S proteins are able to induce protective responses in mice (Honda-Okubo et al, 2015;Li et al, 2013) and the presentation of MERS-CoV full-length S protein as nanoparticles in combination with appropriate adjuvants elicits neutralizing antibodies in immunized mice (Coleman et al, 2014a).…”
Section: Subunit Inactivated and Vectored Vaccines 21 Subunit Vaccmentioning
confidence: 99%
See 1 more Smart Citation
“…Intranasal vaccination with the RBD domain of the MERS-CoV S protein induced much stronger local mucosal immune responses in the lung than subcutaneous immunization (Ma et al, 2014a). Other studies showed that full-length monomeric or trimeric recombinant SARS-CoV and MERS-CoV S proteins are able to induce protective responses in mice (Honda-Okubo et al, 2015;Li et al, 2013) and the presentation of MERS-CoV full-length S protein as nanoparticles in combination with appropriate adjuvants elicits neutralizing antibodies in immunized mice (Coleman et al, 2014a).…”
Section: Subunit Inactivated and Vectored Vaccines 21 Subunit Vaccmentioning
confidence: 99%
“…To increase the duration of immune responses elicited by vaccines and to prevent the CoV-induced lung immunopathology observed after challenge or natural infection, the effects of adjuvants have been studied. In immunizations either with recombinant CoV S protein or with inactivated wholevirus vaccines, the effects of different adjuvants including alum, CpG, and Adva, a new delta-inulin-based polysaccharide adjuvant, were analyzed (Honda-Okubo et al, 2015). While all vaccines protected against lethal infection, addition of an adjuvant significantly increased serum neutralizing antibody titers and reduced lung virus titers on day 3 postchallenge.…”
Section: Vaccine Biosafety 41 Adei and Eosinophilia Inductionmentioning
confidence: 99%
“…Advax adjuvant comprises discoidal shape particles of 1-2 μm in diameter, formed by assembly of a series of lamellar crystalline sheets [23]. Adjuvantation of parenterally administered vaccines with Advax has shown to improve the immunogenicity and protective capacity of several vaccine candidates against hepatitis B, anthrax, severe acute respiratory syndrome (SARS) coronavirus, listeria and influenza [21,[24][25][26][27]. The exact mechanism by which Advax boosts immune responses upon parenteral administration is still under investigation [23].…”
Section: Introductionmentioning
confidence: 99%
“…19 Advax has been shown to provide enhanced vaccine immunogenicity and antigen sparing while having low reactogenicity. 20 It drives a strong T H 1 response that might help suppress any excess T H 2 bias in allergic patients. Notably, when formulated with Advax, vaccines against severe acute respiratory syndrome (SARS) were able to suppress eosinophilic lung pathology after SARS coronavirus infection, whereas this problem was aggravated by formulation of SARS vaccine with the TH2-biasing alum adjuvant.…”
mentioning
confidence: 99%